2018
DOI: 10.5604/12321966.1232771
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities among students of lower secondary schools in Bytom, Poland

Abstract: Introduction and objective. Poverty and low level of education pose the biggest threats to public health. Moreover, they generate inequalities in public healthThe aim of the study was to check if there are any inequalities in health among teenagers living in Bytom, Poland. Materials and method. In 2011 and 2012, an epidemiological cross-sectional study was conducted on 1,099 students from lower secondary schools from Bytom. The students completed a questionnaire which was based on an earlier Health Behaviour i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The diet adopted in one's childhood and adolescence has an impact on eating habits in adulthood. Currently amongst youth, there is an increase in behavioural patterns in direct opposition to those regarded as healthy behaviours, related to lower physical activity, an array of inadequacies in eating habits, including an irregularity or skipping of basic meals, while simultaneously snacking between them [9][10][11][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The diet adopted in one's childhood and adolescence has an impact on eating habits in adulthood. Currently amongst youth, there is an increase in behavioural patterns in direct opposition to those regarded as healthy behaviours, related to lower physical activity, an array of inadequacies in eating habits, including an irregularity or skipping of basic meals, while simultaneously snacking between them [9][10][11][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In the national study Epidemiology of Allergic Diseases in Poland (ECAP), allergy symptoms were found in 40 % of children aged 6-7 and 43 % of children aged 13-14, and BA in 4.4 and 6.5 %, respectively (7). A survey of schoolchildren aged 13-16 revealed that BA prevalence was 9.7 % (8).…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide study called Epidemiology of Allergic Diseases in Poland (ECAP) revealed that features of allergy are present in 40% of children aged 6-7 years and 43% of children aged 13-14 years, whereas asthma affects 4.4% and 6.5%, respectively [3]. A study conducted among schoolchildren in Bytom aged 13-16 years showed the prevalence of bronchial asthma of 9.7% [4]. The increasing prevalence of asthma and allergic diseases may be partly explained by better diagnostic possibilities, growing parental awareness of the symptoms of those disorders as well as the impact of environmental factors, with the home environment being of considerable significance.…”
Section: Introductionmentioning
confidence: 99%